From starting to scaling How to foster startup growth in Europe - Reypens, Charlotte (European Investment Bank, 2020)
High growth startups are widely recognized as key sources of employment, productivity growth and innovation. However, while the long-term impact of the COVID-19 crisis on startups remains to be seen, many now face greater constraints than before. Continued policy support for startups therefore remains vital.In order to guide European policymakers, it is important to understand the key characteristics of high growth startups and gain insights into what sets them apart from other startups. In addition, this report examines the persistent gap between Europe and the United States (US) in terms of startup activity. The findings underscore the role of high growth startups for innovation ecosystems in Europe. The report also highlights some ways governments can continue to support startups by encouraging collaborations with startups as an active innovation partner. The report draws from unique sets of data, including the general module of the European Investment Bank Investment Survey (EIBIS) survey 2019 and the EIBIS Start-up and Scale-up Survey 2019.